Security attacks and challenges in wireless sensor networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (World Scientific Publishing, 2009)
With the advancements of networking technologies and miniaturization of electronic devices, wireless sensor networks (WSN) have become an emerging area of research in academic, industrial, and defense sectors. Sensors combined with low power processors and wireless radios, will see widespread adoption in the new future for a variety of applications including battlefield, hazardous area, and structural health monitoring. However, many issues need to be solved before the full-scale implementations are practical. Among the research issues in WSN, security is one of the most challenging. Securing WSN is challenging because of the limited resources of the sensors participating in the network. Moreover, the reliance on wireless communication technology opens the door for various types of security threats and attacks. Considering the special features of this type of network, in this chapter we address the critical security issues in wireless sensor networks. We discuss cryptography, steganography, and other basics of network security and their applicability to WSN. We explore various types of threats and attacks against wireless sensor networks, possible countermeasures, and notable WSN security research. We also introduce the holistic view of security and future trends for research in wireless sensor network security.